The synthesis of non-structural carbohydrates under the network security model - Chai, Xiaohui; Li, Yuping (Cellular and Molecular Biology, 2020)
In order to explore the pathway of non-structural carbohydrate synthesis, an analysis of the pathway of non-structural carbohydrate synthesis under the network security model was proposed. Taking non-structural carbohydrates as the research object, the experimental materials and equipment were selected under the network security model. Through the establishment of detection methods, the preparation of freeze-dried carbohydrates, the influence of synthesis pathway-specific inhibitors on the synthesis of non-structural carbohydrates, the influence of precursors and intermediates in the pathway on the synthesis of non-structural carbohydrates, the effect of multiple factors on the synthesis of non-structural carbohydrates, the influence of polysaccharide synthesis, the treatment of reaction solution for detection, the preparation of detection sample, the detection conditions of a liquid phase, the detection conditions of LC-MS and the determination of carbohydrate biomass were studied. The results showed that the synthesis of nonstructural carbohydrates requires the participation of the glycolysis, shikimic acid and phenylpropane pathways, but not the polyketone pathway.